New strategies in the field of mixture deconvolution single cell STR profiling. Issue 1 (December 2019) - Anslinger, Katja; Bayer, Birgit
Abstract: STR profiling of single cells isolated by DEPArray™ technology can be used for the successful deconvolution of mixtures composed of cells of the same cell type. In order to gain more information about characteristics and quality of profiles derived from single diploid cells that were separated with the technology mentioned above, a validation study was carried out. Application-specific interpretation guidelines were determined. Under the aspect of occurring drop ins it's essential to always combine several partial profiles attributed to the same person to a consensus profile in order to ensure the derivation of the correct profile. Taking this approach into account, the technique opens up a completely new dimension of mixed stain processing. As shown by an example, this, in principle, also applies to single sperm (haploid cells).